Halliday’s Systemic Functional Linguistics (SFL) Approach and Sports Texts of the Postgraduate Students at Universiti Teknologi Malaysia (Sains Humanika, 2021)
The purpose of this study is to evaluate the scripts entitled ‘‘Sports’’ in terms of processes used and text type based on (Halliday, 1994) Systemic Functional Linguistic approach. Systemic Functional Linguistics (SFL) is looking into the syntactic structure of a clause based on six processes including material, mental and relational process (major category) and verbal, behavioral, and existential processes (minor category). Forty (40) students of the subject ‘Dynamics of Leadership’ at Universiti Teknologi Malaysia were assigned to write essays about ‘Sports’ in between 300—400 words within thirty (30) minutes and sixteen (16) essays were selected for the analysis. Researchers used mixed-method in order to analyze both quantitative (numerical) and qualitative (descriptive) data. All the collected essays were analyzed and then the percentage of all the six processes has been shown in descriptive statistics and interpreted in tabulations and bar graphs. The findings indicate that the dominant process used in all the scripts was material—doing and happening— and subsequently relational. Focusing more on nominalization, the analyzed manuscripts were found to be wordy.
Keywords: Students' Writing; Systematic Functional Linguistics; Transitivity; Process Types